2016
DOI: 10.1111/bjop.12185
|View full text |Cite
|
Sign up to set email alerts
|

Hearing visuo‐tactile synchrony – Sound‐induced proprioceptive drift in the invisible hand illusion

Abstract: The rubber hand illusion (RHI) and its variant the invisible hand illusion (IHI) are useful for investigating multisensory aspects of bodily self-consciousness. Here, we explored whether auditory conditioning during an RHI could enhance the trisensory visuo-tactile-proprioceptive interaction underlying the IHI. Our paradigm comprised of an IHI session that was followed by an RHI session and another IHI session. The IHI sessions had two parts presented in counterbalanced order. One part was conducted in silence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Additionally, in a motor version of the RHI, whereby VR was used to create a virtual xylophone that provided synchronous visual, tactile, and auditory (musical) input -auditory cues were found to enhance the ratings of embodiment given during this virtual hand illusion (Choi et al, 2016). While these latter two studies (Choi et al, 2016;Darnai et al, 2017) use only veridical auditory cues, their findings provide further support for the effect of sound on body ownership.…”
Section: Skin Perception (Parchment Skin Illusion)mentioning
confidence: 76%
See 1 more Smart Citation
“…Additionally, in a motor version of the RHI, whereby VR was used to create a virtual xylophone that provided synchronous visual, tactile, and auditory (musical) input -auditory cues were found to enhance the ratings of embodiment given during this virtual hand illusion (Choi et al, 2016). While these latter two studies (Choi et al, 2016;Darnai et al, 2017) use only veridical auditory cues, their findings provide further support for the effect of sound on body ownership.…”
Section: Skin Perception (Parchment Skin Illusion)mentioning
confidence: 76%
“…Largely consistent effects on body ownership were seen for non-naturalistic auditory cues. When auditory input (the sound of a metronome) was paired with an invisible hand illusion (stroking the real hand and stroking an empty area of space such that the space is 'embodied), the effect of the illusion was stronger (in terms of the magnitude of the proprioceptive drift observed) than when no auditory cues were present (Darnai et al, 2017). Additionally, in a motor version of the RHI, whereby VR was used to create a virtual xylophone that provided synchronous visual, tactile, and auditory (musical) input -auditory cues were found to enhance the ratings of embodiment given during this virtual hand illusion (Choi et al, 2016).…”
Section: Skin Perception (Parchment Skin Illusion)mentioning
confidence: 99%
“…Another aspect of tactile stimuli and/or movements within the RHI paradigm consists in concurring auditory cues (e.g., tapping sounds of a moving finger). From a methodological point of view, this is an important -though often overlooked -detail, because it has recently been shown that synchronous auditory cues (i.e., in addition to synchronous visuotactile stimulation) can enhance proprioceptive drift in the RHI (Darnai et al, 2017;Radziun and Ehrsson, 2018). As in most studies it is not reported whether auditory cues were eliminated (e.g., by earplugs) or not, it is difficult to exclude this potential source of inconsistencies between studies.…”
Section: Properties Of the Tactile Stimuli And Type Of Movementsmentioning
confidence: 99%
“…In 2017, examples for the wide range of current research represented in this journal are easily identified. They include not only the target article on language development (Vihman, ) and its possible parallels to the development of face processing (Pascalis, Dole, & Loevenbruck, ), but also new findings from multisensory perception (Darnai et al ., ); visual attention and cultural differences (Amer, Ngo, & Hasher, ); on peers’ influences on risk taking in young adulthood (Reniers et al ., ); on the psychology of mobile gambling behaviour (James, O'Malley, & Tunney, ); adverse consequences of conspiracy theories in the work context (Douglas & Leite, ); or, last but not least, a paper that originated from a high‐profile symposium on face processing held at the BPS Cognitive Psychology Section Annual Conference in 2015 (Davies & Young, ), and that describes the rise and continued success of face processing research since Haydn Ellis had published his seminal review on the topic in this journal (Ellis, ).…”
Section: Some Ideas For Future Directionsmentioning
confidence: 99%